Deletion of Kcnj16 in Mice Does Not Alter Auditory Function - Lv, Jun; Fu, Xiaolong; Li, Yige; Hong, Guodong; Li, Peipei; Lin, Jing; Xun, Youfang; Fang, Lucheng; Weng, Weibin; Yue, Rongyu; Li, Geng-Lin; Guan, Bing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Endolymphatic potential is the main driving force behind the sensory transduction of hearing, and K+ is the main charge carrier. Kir5.1 is a K+ transporter that plays a significant role in maintaining endolymphatic potential homeostasis, but the expression pattern and role of Kir5.1 (which is encoded by the Kcnj16 gene) in the mouse auditory system has remained unclear. In this study, we found that Kir5.1 was expressed in the mouse cochlea. We checked the inner ear morphology and measured auditory function in Kcnj16–/– mice and found that loss of Kcnj16 did not appear to affect the development of hair cells. There was no significant difference in auditory function between Kcnj16–/– mice and wild-type littermates, although the expression of Kcnma1, Kcnq4, and Kcne1 were significantly decreased in the Kcnj16–/– mice. Additionally, no significant differences were found in the number or distribution of ribbon synapses between the Kcnj16–/– and wild-type mice. In summary, our results suggest that the Kcnj16 gene is not essential for auditory function in mice.